On connected m multiply 2 dimensions hyperplane complete residual graph. Issue 4 (3rd July 2016) - Duan, Huiming; Liu, Yixin; Wang, Kun; You, Meilin
Abstract: In this paper, we extend P.Erdös, F.Harary and M.Klawe's definition of plane complete residual graph to hyperplane and define 2 dimensions hyperplane complete graph. We obtain the minimum order of 2 dimensions hyperplane complete-residual graphs and the minimum order of m multiply 2 dimensions hyperplane complete-residual graphs. In addition, we obtain a unique 2 dimensions hyperplane complete-residual extremal graph and a unique m multiply 2 dimensions hyperplane complete-residual extremal graph.